2018
DOI: 10.12659/msm.907734
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Treatment Regulates SIRT3 Expression in Early Brain Injury (EBI) Due to Reactive Oxygen Species (ROS) in a Mouse Model of Subarachnoid Hemorrhage (SAH)

Abstract: BackgroundA mouse model of subarachnoid hemorrhage (SAH) investigated the effects of melatonin treatment on the generation of reactive oxygen species (ROS) and the activation of the SIRT3 gene in early brain injury (EBI).Material/MethodsMale C57BL/6J mice were assigned to three groups: the SAH group; the sham group; and the SAH + melatonin-treated group (intraperitoneal dose, 150 mg/kg). TUNEL was used to study apoptosis of neuronal cells, Western-blot and immunohistochemistry detected expression of Sirt3, Bcl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…Melatonin is reported to exert both direct free radical scavenging and antioxidative effects, thereby preventing the production of ROS that damage cell membranes. 26 Consistent with the above observations, the protective effect of melatonin was further proved by reduced oxidative stress as manifested by decreased lipid peroxidation (less generation of MDA and larger GSH/GSSG ratio) and increased antioxidant capacity (higher SOD and catalase activities). We further demonstrated that melatonin pretreatment significantly limited pro-inflammatory cytokine production and neutrophil and macrophage infiltration, all of which are evoked by IR injury and considered major mediator of acute kidney injury.…”
Section: Discussionsupporting
confidence: 81%
“…Melatonin is reported to exert both direct free radical scavenging and antioxidative effects, thereby preventing the production of ROS that damage cell membranes. 26 Consistent with the above observations, the protective effect of melatonin was further proved by reduced oxidative stress as manifested by decreased lipid peroxidation (less generation of MDA and larger GSH/GSSG ratio) and increased antioxidant capacity (higher SOD and catalase activities). We further demonstrated that melatonin pretreatment significantly limited pro-inflammatory cytokine production and neutrophil and macrophage infiltration, all of which are evoked by IR injury and considered major mediator of acute kidney injury.…”
Section: Discussionsupporting
confidence: 81%
“…The work demonstrated that melatonin upregulated mitophagy‐associated proteins and reduced ROS generation, thus inhibiting NLRP3 inflammasome activation. In a report this year, SIRT3 protein expression enhanced by melatonin was observed to reduce ROS, then inhibit NLRP3 inflammasome activation and protect neuronal cells . SIRT3 protein locates at mitochondria and is associated with mitophagy , which may be one main target of melatonin regulating ROS‐NLRP3 inflammasome pathway, as illustrated in Fig.…”
Section: Treatment Of Antioxidants For Suppressing Nlrp3 Inflammasomementioning
confidence: 93%
“…Many of them clear ROS through enhancing antioxidase expression via Nrf2 pathway, thus regulating ROS‐mediated NLRP3 inflammasome expression and/or activation. Autophagy, including mitophagy, may also mediate ROS reduction and suppress NLRP3 inflammatory signaling pathway . Activation of autophagy and decreased ROS production was observed when quercetin suppressed NLRP3 inflammasome activation in epithelial cells infected with E. coli O157:H7 .…”
Section: Treatment Of Antioxidants For Suppressing Nlrp3 Inflammasomementioning
confidence: 98%
See 1 more Smart Citation
“…Melatonin is a powerful antioxidant that attenuates early brain injury-induced oxidative stress and neuronal apoptosis by activating the SIRT1/NF-kB pathway (Zhao et al, 2017). Furthermore, melatonin upregulates the expression of SIRT3 to reduce the production of ROS and resist oxidative stress (Yang et al, 2018). Estrogen also regulates SIRT1.…”
Section: Sirtuins As Promising Therapeutic Targetsmentioning
confidence: 99%